2018
DOI: 10.21873/anticanres.12578
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neutrophil–to–Lymphocyte Ratio Predicts Survival in Patients with Advanced Gastric Cancer Treated with Trastuzumab Combination Chemotherapy

Abstract: This study found that a high NLR was associated with a shorter PFS and OS in patients with HER2-positive gastric cancer treated with trastuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Recognized independent prognostic factors affecting the survival of AGC include tumor-related factors and systemic inflammatory factors [4]. Various hematological markers, such as neutrophil to lymphocyte ratio (NLR), C-reactive protein (CRP), and plasma fibrinogen levels, have been reported as effective prognostic indicators of AGC [58]. However, other laboratory markers which are widely available and inexpensive are also needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recognized independent prognostic factors affecting the survival of AGC include tumor-related factors and systemic inflammatory factors [4]. Various hematological markers, such as neutrophil to lymphocyte ratio (NLR), C-reactive protein (CRP), and plasma fibrinogen levels, have been reported as effective prognostic indicators of AGC [58]. However, other laboratory markers which are widely available and inexpensive are also needed.…”
Section: Introductionmentioning
confidence: 99%
“…The median DFS time was 54 months. Neutrophil to lymphocyte ratio (NLR) has been analyzed in connection with several types of cancer including lung cancer [15], gastric cancer [16], colorectal cancer [17], pancreatic cancer [18], hepatocellular carcinoma [8], ovarian cancer [19], and some hematological malignancies [20]. And low NLR ratios have been associated…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports on the prognostic value of NLR in AGC were consistent with our study. 12,[19][20][21] An elevated NLR has been shown to be associated with reduced OS and PFS in patients with HER2-positive AGC. Clinical studies have shown the relationship between NLR and tumor response to chemotherapy in metastatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Several studies have shown that NLR before chemotherapy can help predict the prognosis of AGC progression. 12,[19][20][21] However, there is limited data on the clinical and prognostic significance of HER2 gene amplification and NLR in…”
mentioning
confidence: 99%
See 1 more Smart Citation